Clinical study on S-1108 in the treatment of respiratory tract infections - Yamaguchi, Etsuro; Kawakami, Yoshikazu (CHEMOTHERAPY, 1993)
To evaluate the usefulness of the novel and oral esterified cephem antibiotic S-1108 in respiratory infections, we conducted a clinical trial. The study subjects included 5 patients with respiratory tract infection (1 male and 4 females; age, 34 to 69 yr). S-1108 was administered orally in doses of 100 to 200 mg t. i. d. for 3 to 14 days. Clinical effects were good in 2 cases, fair in 2, and poor in 1. The overall efficacy rate was 2/5. No side effects or abnormal laboratory data were observed.